Investigating the Effect of Board Characteristics and CEO Tenure on Audit Quality in Companies Listed on the Iraq and Qatar Stock Exchanges: A Comparative Approach - Rashid Al-Bugharbee , Read Naeem; Mohammadi Khoshouei, Hamzeh; Manhal Abu-Ragheef, Ismael Abbas; Saedi, Rahman (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective:  This study aims to examine the impact of board characteristics and CEO tenure on audit quality in companies listed on the Iraq and Qatar stock exchanges, with a comparative analysis of these two emerging markets.Methodology: The study employs a quantitative resesarch design using panel data regression analysis to assess the relationships between board size, board independence, CEO tenure, and institutional ownership with audit quality. The research sample consists of 232 firm-year observations from Iraq and 176 firm-year observations from Qatar, covering the period 2015 to 2022. Data were collected from financial statements and corporate reports of publicly listed companies. To ensure robustness, unit root tests, variance heterogeneity tests (White test), and multicollinearity diagnostics (VIF values) were conducted before hypothesis testing. The hypotheses were tested using regression models based on McFadden’s logit estimation, and model fit was evaluated through Likelihood Ratio (LR) statistics and McFadden's R² values.Findings: The results indicate a significant positive relationship between board size and audit quality in Iraq, whereas no significant relationship was found in Qatar. Board independence positively and significantly influences audit quality in both countries. CEO tenure is positively associated with higher audit quality, supporting the stewardship and resource dependence theories. However, institutional ownership has a significant negative effect on audit quality, suggesting that higher institutional investor influence may reduce auditor independence. The McFadden R² values range from 16% to 45%, demonstrating that corporate governance variables significantly explain variations in audit quality across firms in Iraq and Qatar.Conclusion: The findings suggest that stronger governance regulations may be required to mitigate institutional investor influence and enhance audit transparency, particularly in emerging markets.